Innovative inlet air cooling technology for gas turbine power plants using integrated solid desiccant and Maisotsenko cooler - Saghafifar, Mohammad (2015)
Gas turbine thermal efficiency has significant dependency on climatic conditions. Evaporative cooling is commonly utilized as an inlet air cooling technique in hot and dry climates though an increase in atmospheric humidity will considerably diminish its performance. Implementing desiccants to dehumidify air will enhance evaporative inlet cooling effectiveness. Furthermore, a recently commercialized cooler named Maisotsenko cooler can be integrated in gas turbine inlet air cooling to replace conventional evaporative coolers. In this paper, four different inlet air cooling systems employing turbine waste heat are proposed for gas turbine power augmentation in hot and humid climates such as UAE. Detailed sensitivity analysis is performed to investigate the impact of ambient air conditions and regeneration temperature on the inlet air cooling systems' effectiveness. Recommended inlet air cooling techniques are evaluated against more commonly used inlet air cooling systems under UAE climatic conditions. Finally, economic and transient analysis are accomplished to signify the most economical inlet air cooling system that is most suitable for UAE gas turbine power augmentation. Maisotsenko evaporative desiccant inlet air cooling with life savings of 31.882 MUS$ is the most economically justified inlet cooling technique for a 50 MWe gas turbine power plant in UAE with life span of 25 years.